An atlas of Michigan fishes with keys and illustrations for their identification - Bailey, Reeve M.; Latta, William C.; Smith, Gerald R. (Ann Arbor, Michigan The University of Michigan, 2004)
Miscellaneous Publications, Museum of Zoology, University of Michigan no. 192
Keywords: Fishes--Great Lakes--Identification.; Fishes--Atlases.